Controller cooling of an electric vehicle: An analytical and CFD study of heat transfer - Rahman M.M.; Rahman H.Y.; Hua T.J. (American Institute of Physics Inc., 2023)
This paper presents the analytical and CFD studies of heat transfer from the heat sink of the controller of an electric vehicle (EV). Maximum heat generation from the controller during the operation of the EV was calculated and a forced air cooled heat sink with fin was designed to remove this heat. Heat removal from the finned heat sink was calculated analytically at different air velocity. Heat transfer performance was also simulated through commercially available CFD software at different air velocity. The results revealed that at an air velocity of 15 m/s is capable to remove the targeted heat from the heat sink to maintain the controller at a range of suitable operating temperature. 2015 AIP Publishing LLC.